Venovenous Extracorporeal Life Support in Single-Ventricle Patients with Acute Respiratory Distress Syndrome - Nair, Alison B.; Oishi, Peter (Frontiers in Pediatrics, 2016)
There is new and growing experience with venovenous extracorporeal life support (VV ECLS) for neonatal and pediatric patients with single ventricle physiology and acute respiratory distress syndrome (ARDS). Outcomes in this population have been defined but could be improved; survival rates in single ventricle patients on VV ECLS for respiratory failure are slightly higher than in single ventricle patients on venoarterial ECLS for cardiac failure (48% vs 32-43%), but are lower than in patients with biventricular anatomy (58%-74%). To that end, special consideration is necessary for patients with single ventricle physiology who require VV ECLS for ARDS. Specifically, ARDS disrupts the balance between pulmonary and systemic blood flow through dynamic alterations in cardiopulmonary mechanics. This complexity impacts how to run the VV ECLS circuit and the transition back to conventional support. Further, these patients have a complicated coagulation profile. Both venous and arterial thrombi carry marked risk in single ventricle patients due to the vulnerability of the pulmonary, coronary, and cerebral circulations. Finally, single ventricle palliation requires the preservation of low resistance across the pulmonary circulation, unobstructed venous return, and optimal cardiac performance including valve function. As such, the proper timing as well as the particular conduct of ECLS might differ between this population and patients without single ventricle physiology. The goal of this review is to summarize the current state of knowledge of VV ECLS in the single ventricle population in the context of these special considerations.